2017
DOI: 10.21037/gs.2017.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Robotic retroauricular thyroidectomy: initial experience from India

Abstract: Robotic thyroidectomy is getting accepted worldwide, but, majority of the literature is from South Korea. The purpose of this paper is to review the early experiences with robotic retroauricular (RA) thyroidectomy from India. The rationale for robotic thyroidectomy, its advantages and disadvantages are reviewed. The reasons for selecting the RA approach and the criteria used for selecting the patients are discussed. The early experience and outcomes of 29 patients, from three centres across India is presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The recurrent laryngeal nerve is identified within the tracheoesophageal groove. Finally, the relevant lobe of the thyroid is removed from the trachea by cutting the isthmus [3,5].…”
Section: Robotic Retroauricular Thyroidectomymentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrent laryngeal nerve is identified within the tracheoesophageal groove. Finally, the relevant lobe of the thyroid is removed from the trachea by cutting the isthmus [3,5].…”
Section: Robotic Retroauricular Thyroidectomymentioning
confidence: 99%
“…Robotic surgical techniques have advanced particularly rapidly in countries such as South Korea, Japan, and China, where there is considerable cultural pressure to reduce the scarring associated with head and neck surgery. This includes the development of novel Transaxillary, Transoral, and Retroauricular techniques [3,4]. Terris et al first described Robotic Retroauricular Thyroidectomy (RRT) in 2011, as 'robotic facelift thyroidectomy' [5].…”
Section: Introductionmentioning
confidence: 99%
“…Robotic retroauricular (RA) thyroidectomy, one of the most recently spotlighted remote access surgical techniques of thyroidectomy, has been developed and actively practiced by several robotic surgeons to overcome certain limitations of the former robotic transaxillary (TA) thyroidectomy. 6,7 There have been successful reports of the robotic RA thyroidectomy by many institutions worldwide. 6,7 Julia et al reported feasibility of RA thyroidectomy with a single-arm robotic surgical system in a preclinical cadaveric setting.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 There have been successful reports of the robotic RA thyroidectomy by many institutions worldwide. 6,7 Julia et al reported feasibility of RA thyroidectomy with a single-arm robotic surgical system in a preclinical cadaveric setting. They demonstrated that during RA thyroidectomy, SP robotic system facilitated more efficient dissection by allowing additional retraction of surrounding gland or tissue and that robotic surgical system might have the potential to replace current systems for RA thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, remote access surgery has become the standard of care for the cosmetically inclined patient and surgeon. The efforts to reduce access path to the thyroid evolved towards retroauricular robotic access,[ 4 5 ] which is currently the most commonly performed remote access thyroid surgery.…”
mentioning
confidence: 99%